2010
DOI: 10.1007/s11064-010-0336-7
|View full text |Cite|
|
Sign up to set email alerts
|

Estrogen or Estrogen Receptor Agonist Inhibits Lipopolysaccharide Induced Microglial Activation and Death

Abstract: Inflammation is an important pathogenic mechanism in many neurodegenerative disorders. Activated microglia play a pivotal role in releasing proinflammatory factors including interleukin-1 (IL-1), tumor necrosis factor-α (TNF-α), and cyclooxygenase-2 (COX-2) for inducing inflammation. While microglia mediated inflammation is essential in maintaining CNS homeostasis, chronic inflammation results in activation of proteases for cell death. Here, we examined the effect of PPT (estrogen receptor α agonist), DPN (est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
47
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 37 publications
7
47
1
Order By: Relevance
“…They found that neonatal LPS exposure at postnatal day 14 caused elevated basal expression of hypothalamic COX-2 in the male, but not in the female rats. Similarly, Smith et al (2011) found that estrogen or estrogen receptor agonists inhibited LPS-induced microglial activation and death in the brain in rats. Specifically, estrogen prevented cell death by attenuating the release of interleukin-1-alpha, interleukin-1-beta, tumor necrosis factor-α, and COX-2.…”
Section: Why Males Might Be More Vulnerablementioning
confidence: 87%
“…They found that neonatal LPS exposure at postnatal day 14 caused elevated basal expression of hypothalamic COX-2 in the male, but not in the female rats. Similarly, Smith et al (2011) found that estrogen or estrogen receptor agonists inhibited LPS-induced microglial activation and death in the brain in rats. Specifically, estrogen prevented cell death by attenuating the release of interleukin-1-alpha, interleukin-1-beta, tumor necrosis factor-α, and COX-2.…”
Section: Why Males Might Be More Vulnerablementioning
confidence: 87%
“…Previous studies suggest that hormone therapy could modulate TME which then induces treatment resistance. Specifically, it has been observed that cytokine profile in the TME was changed upon ERα suppression, for example, IL-1β level is significantly unregulated [107]. In presence of IL-1β, tamoxifen acts as an agonist rather than an antagonist, and promotes tumor progression [108].…”
Section: Hormonal Therapymentioning
confidence: 99%
“…The inhibitory effects of PPT and DPN on many neurological disorders have been confirmed by other studies. 7,18,32,45,53 The receptors ERa and ERb are essential for E2-mediated regulation of BBB permeability, antiinflammatory properties, the production of interleukins in the brain, and regulation of neutrophil recruitment into the brain. 7 Both ER agonists reduce the inflammatory response 45 and take part in the control of inflammation by estradiol, 18 neuromodulation, and neuroprotection processes after brain injury.…”
mentioning
confidence: 99%
“…7,18,32,45,53 The receptors ERa and ERb are essential for E2-mediated regulation of BBB permeability, antiinflammatory properties, the production of interleukins in the brain, and regulation of neutrophil recruitment into the brain. 7 Both ER agonists reduce the inflammatory response 45 and take part in the control of inflammation by estradiol, 18 neuromodulation, and neuroprotection processes after brain injury. 27,34,53 There are several probable mechanisms by which ERa and ERb attenuate BBB permeability and brain edema after TBI that result from the inflammatory response: upregulation of defensin genes, IL-6, MMP-9, MHC (major histocompatibility complex) antigen genes, and some of phagocytic receptors; 40,54 protection of cortical cells against oxidative glutamate toxicity; 59 neuroprotection of estrogen against activated microglia; 4 inhibition of the cytoplasmic transport of NF-kB (a transcription factor for inflammatory genes); 54,56 induction of activity of the phosphoinositol-3 kinase and Akt;…”
mentioning
confidence: 99%